Protein Carbamylation in Peritoneal Dialysis and the Effect of Low Glucose plus Amino Acid Solutions. Issue 2 (March 2018) - Trottier, Caitlin; Perl, Jeffrey; Freeman, Megan; Thadhani, Ravi; Berg, Anders; Kalim, Sahir
Protein carbamylation is a post-translational urea-driven protein modification associated with mortality. Free amino acids (AAs) competitively inhibit protein carbamylation and parenteral AA therapy reduces carbamylation in hemodialysis (HD) patients. Peritoneal dialysis (PD) yields differences in urea clearance and AA balance compared with HD, but the influence of PD and intraperitoneal AA solutions on carbamylation is unclear. Thus, we first measured carbamylated albumin (C-Alb; a marker of carbamylation load) in 100 diabetic HD patients frequency-matched by age, sex, and race to 98 diabetic PD subjects from the IMPENDIA trial, which originally compared the metabolic effects of low-glucose PD solutions (incorporating icodextrin and AAs) to a control group (dextrose-only solutions). We then determined the effects of the AA-enriched PD solutions by measuring the 6-month change in C-Alb within the IMPENDIA cohort by treatment allocation (48 treated vs 50 controls). Peritoneal dialysis patients, when compared with HD patients, had higher baseline urea and higher C-Alb. Among IMPENDIA participants, there was no difference in C-Alb change in either arm, but treated subjects showed a trend towards increased carbamylation. Treated subjects also demonstrated an increase in urea, possibly explaining the carbamylation trend. In summary, carbamylation levels in PD patients appeared higher than in matched HD patients. A regimen of AA and low-glucose PD solutions did not reduce C-Alb in IMPENDIA subjects.